Protective Effects of Emodin on Oxidized Fish Oil-Induced Metabolic Disorder and Oxidative Stress through Notch-Nrf2 Crosstalk in the Liver of Teleost Megalobrama amblycephala - Changyou Song; Bo Liu; Hongxia Li; Yongkai Tang; Xianping Ge; Bo Liu; Pao Xu (MDPI AG, 2022)
Dietary oxidized lipids are key perpetrator to accumulate excessive reactive oxygen species (ROS) that induce oxidative stress for animals. Immoderate oxidative stress dysregulates cell fate, perturbs cellular homeostasis, thereby interrupts metabolism and normal growth. Therefore, a 12-week feeding trial with fish oil (FO, control group), oxidized fish oil (OF), and emodin-supplemented (OF+E) diets was conducted to evaluate the therapeutic mechanism of emodin on metabolic and oxidative resistance in Megalobrama amblycephala liver. Morphologically, emodin remits oxidized fish oil-induced cellular constituents damage, evidenced by lipid droplets enlargement and accumulation, mitochondria rupture, and nucleus aggregation, which were functionally related to oxidative stress, metabolism, and cell fate determination. Consecutively, glucose, lipid, and amino acid metabolism were retained under emodin stimulation. Specifically, fatty acid metabolic genes optimized fatty acid utilization and metabolism, featured as total saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA) alternation. Physiologically, inflammation, autophagy, apoptosis, as well as antioxidant capacity were alleviated by emodin. Interactively, fatty acid metabolism was correlated with antioxidant capacity; while the crosstalk and dynamic equilibrium between apoptosis and autophagy determine the cell fate under oxidative stress amelioration. Synergistically, Nrf2 and Notch signaling were active to antioxidant defense. In particular, oxidative stress blocked the crosstalk between Notch and Nrf2 signaling, while emodin rescued Notch-Nrf2 interaction to ameliorate oxidative stress. In conclusion, these results suggest that elevated ROS levels by oxidative stress activates Notch and Nrf2 signaling but intercepts Notch-Nrf2 crosstalk to stimulate cell fate and antioxidant program; dietary emodin alleviates oxidative stress and returns overall ROS levels to a moderate state to maintain homeostatic balance. The crosstalk between Notch and Nrf2 signaling might be the potential therapeutic target for emodin to ameliorate oxidative stress and metabolic disorder in M. amblycephala liver.